Revitalisasi Pendidikan Dharmagita Pada Generasi Muda Di Provinsi Nusa Tenggara Barat - Wiasti, Ni Komang (Jurnal Penelitian Agama Hindu, 2025)
Dharmagita education in the province of West Nusa Tenggara is experiencing a decline in interest among the younger generation due to modernisation and globalisation, which shifts their attention from spiritual cultural heritage to digital entertainment. This phenomenon raises concerns about the preservation of Hindu religious values and traditional culture. This research will explore strategies for revitalising Dharmagita education for the Hindu youth in NTB through an integrative approach that includes formal education, non-formal pasraman, art communities, the use of digital technology, and competition activities. This research employs a descriptive qualitative method, utilising data collection techniques such as interviews, observations, and documentation involving Dharmagita practitioners, educators, and members of the Hindu community. The research results show that effective revitalisation is achieved by integrating Dharmagita learning into school and pasraman curricula, providing teacher training, utilising interactive digital media, and regularly organising Dharmagita competitions as a form of appreciation and stimulation for the younger generation. In addition, the revival of this tradition as a component of character building and religious identity formation requires active involvement from families, communities, and religious institutions. This research concludes that the revitalisation of Dharmagita is an important strategy for preserving Hindu culture, strengthening the moral and spiritual values of the Hindu youth in NTB, and serving as a model of education based on local wisdom that is relevant to the challenges of the digital era.